Advancing the Understanding of Adaptive Capacity of Social‐Ecological Systems to Absorb Climate Extremes - Kirsten Thonicke; Michael Bahn; Sandra Lavorel; Richard D. Bardgett; Karlheinz Erb; Mariasilvia Giamberini; Markus Reichstein; Björn Vollan; Anja Rammig (Earth's Future, 2020)
Abstract Enhancing the capacity of social‐ecological systems (SES) to adapt to climate change is of crucial importance. While gradual climate change impacts have been the main focus of much recent research, much less is known about how SES are impacted by climate extremes and how they adapt. Here, based on an advanced conceptualization of social‐ecological resilience, performed by an interdisciplinary group of scientists, we outline three major challenges for operationalizing the resilience concept with particular focus on climate extremes. First, we discuss the necessary steps required to identify and measure relevant variables for capturing the full response spectrum of the coupled social and ecological components of SES. Second, we examine how climate extreme impacts on coupling flows in SES can be quantified by learning from past societal transitions or adaptations to climate extremes and resulting changes in ecosystem service supply. Last, we explore how to identify management options for maintaining and enhancing social‐ecological resilience under a changing regime of climate extremes. We conclude that multiple pathways within adaptation and mitigation strategies which enhance the adaptive capacity of SES to absorb climate extremes will open the way toward a sustainable future.